2006
DOI: 10.1002/jccs.200600157
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Chemoselective Reaction of Aldehydes with 2‐Mercaptoethanol Catalyzed by SiO2‐NaHSO4 under Solvent‐free Condition

Abstract: An efficient and user-friendly procedure has been developed for the chemoselective protection of aldehyde carbonyl groups such as bis(2-hydroxyethyl)dithioacetals with 2-mercaptoethanol catalyzed by silica-supported sodium bisulphate under solvent-free conditions. It has been shown that a variety of aldehydes can expeditiously undergo this reaction to produce their corresponding dithioacetals with impressive yields at room temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…An efficient and solvent free synthesis of ChrCH(OAc) 2 and its deprotection to ChrCHO catalyzed by reusable Envirocat EPZ10R under microwave irradiation has been claimed by Shindalkar et al 20 Conversion of ChrCHO into ChrCH(SCH 2 CH 2 OH) 2 with mercaptoethanol is catalyzed by silica supported sodium sulphate under solvent free condition. 21 Indium trifluoride catalyzed protection of the aldehyde group of ChrCHO with MeOH, PhCH 2 OH, 2,2-dimethylpropane-1,3-diol, PhSH, HSCH 2 CH 2 SH, HSCH 2 CH 2 CH 2 SH in refluxing toluene is known. 22 Acetal as well as thioacetal of ChrCHO when refluxed in MeCN-…”
Section: Radical Additionmentioning
confidence: 99%
“…An efficient and solvent free synthesis of ChrCH(OAc) 2 and its deprotection to ChrCHO catalyzed by reusable Envirocat EPZ10R under microwave irradiation has been claimed by Shindalkar et al 20 Conversion of ChrCHO into ChrCH(SCH 2 CH 2 OH) 2 with mercaptoethanol is catalyzed by silica supported sodium sulphate under solvent free condition. 21 Indium trifluoride catalyzed protection of the aldehyde group of ChrCHO with MeOH, PhCH 2 OH, 2,2-dimethylpropane-1,3-diol, PhSH, HSCH 2 CH 2 SH, HSCH 2 CH 2 CH 2 SH in refluxing toluene is known. 22 Acetal as well as thioacetal of ChrCHO when refluxed in MeCN-…”
Section: Radical Additionmentioning
confidence: 99%
“…SiO 2 -NaHSO 4 catalyst was prepared by the reported method [18]. Silica gel (15 g, 100-200 mesh) was added to a magnetically stirred solution of NaHSO 4 .H 2 O (6.9 g, 50 mmol) in distilled water (100 ml) at 25 °C over a 30 min period.…”
Section: Preparation Of the Catalystmentioning
confidence: 99%
“…A literature survey revealed that the use of SiO 2 -NaHSO 4 for the synthesis of xanthenediones [19], ȕ-enaminones, and 2-methylquinolin-4(1H)-ones [20]. Furthermore, SiO 2 -NaHSO 4 has been used in the protection of aldehydes with 2-mercaptoethanol [18]. In a continuation of our work into the synthesis of biologically active heterocyclic compounds using readily available, inexpensive, and environment friendly catalysts [21][22][23][24][25][26], herein we are report the synthesis of octahydro-quinazolin-2,5-diones by the one-pot multi-component reaction of aromatic aldehydes, dimedone, and urea using SiO 2 -NaHSO 4 as an efficient catalyst in water.…”
Section: Catalytic Performance Of Sio 2 -Nahsomentioning
confidence: 99%
See 1 more Smart Citation
“…1 The carbonyl protection using SH often competes with nucleophilic reactions 2 and SH group is sensitive to the oxidation by dimerization and S-oxide formation.…”
Section: Introductionmentioning
confidence: 99%